2021
DOI: 10.1162/jocn_a_01705
|View full text |Cite
|
Sign up to set email alerts
|

Neural Repetition Suppression Modulates Time Perception: Evidence From Electrophysiology and Pupillometry

Abstract: Human time perception is malleable and subject to many biases. For example, it has repeatedly been shown that stimuli that are physically intense or that are unexpected seem to last longer. Two competing hypotheses have been proposed to account for such biases: One states that these temporal illusions are the result of increased levels of arousal that speeds up neural clock dynamics, whereas the alternative “magnitude coding” account states that the magnitude of sensory responses causally modulates perceived d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 128 publications
10
25
1
Order By: Relevance
“…This behavioral bias coincided with ERP differences in response to the offset markers of "Same" and "Opposite" markers, a finding that warrants more thorough exploration beyond the scope of this study. We discuss this observation in more detail in a companion paper (Kruijne et al, 2021).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This behavioral bias coincided with ERP differences in response to the offset markers of "Same" and "Opposite" markers, a finding that warrants more thorough exploration beyond the scope of this study. We discuss this observation in more detail in a companion paper (Kruijne et al, 2021).…”
Section: Discussionmentioning
confidence: 81%
“…The EEG results presented below offer tentative evidence that this finding relates to the neural response evoked by the offset marker in "Opposite" blocks. However, as this does not immediately relate to the current research question, we have presented a more in-depth investigation elsewhere (Kruijne, Olivers, & van Rijn, 2021). In this paper, EEG analyses will focus on neural markers for memory maintenance and retrieval.…”
Section: Behaviormentioning
confidence: 99%
“…In particular, we found that change bias effects on duration perception were found with visual stimuli that differed in location, size and numerosity, but not with any of the other tested feature dimensions. In an earlier study we have demonstrated that the change bias manifests when stimuli marking the start and end of an interval either repeat or change in location (Kruijne et al, 2021). The results suggested that sensory responses to the offset marker were attenuated upon repetition compared to changes, which in turn affected the perceived duration.…”
Section: Feature Changes Affect Time Perceptionmentioning
confidence: 90%
“…This hypothesis-driven model makes several assumptions that were based on our earlier findings (Kruijne et al, 2021). Most importantly, the model assumes that experimental conditions (trial type and block type) only differ with respect to the shift of the psychometric curves, but not their slope.…”
Section: Stimuli and Materials Stimuli Were Presented On An Lg-22mb37 Led Monitormentioning
confidence: 99%
See 1 more Smart Citation